Nutritional and Phytochemical Variation of Marula (Sclerocarya birrea) (Subspecies caffra and birrea) Fruit among Nine International Provenances Tested in Malawi - Mussa Kamanula; Chimuleke Yagontha Munthali; John Finias Kamanula (International Journal of Food Science)
Sclerocarya birrea (Marula) is one of the indigenous fruit trees that was selected for domestication in Malawi. This study was conducted to assess nutritional and phytochemical variation of Sclerocarya birrea (subspecies caffra and birrea) fruits planted in an international provenance trial in Malawi. Vitamin C, calcium, iron, zinc, fat, and fibre content ranged from 6 to 81 mg/100 g; 1.8 to 5.3 mg/100 g; 1.4 to 3.3 mg/100 g; 0.3 to 0.8 mg/100 g; 51.6 to 57.7%; and 4.1 to 6.9%, respectively. Phytochemical scores showed that all nine provenances contained weak (+) concentration of alkaloids. Kalimbeza (Namibia) and Magamba-Turiani (Tanzania) provenances showed moderate (++) concentrations of saponins. Chikhwawa (Malawi), Missira (Mali), and Moamba (Mozambique) provenances had moderate (++) concentrations of tannins. Missira (Mali) and Kalimbeza (Namibia) provenances showed weak (+) concentration of terpenoids. Variations observed in nutritional and phytochemical composition could be attributed to genetic make-up and origin of the genotypes, since all genotypes were planted in the same environment. Therefore, selection of Sclerocarya birrea for domestication purposes should consider the provenance (origin of genotypes) and subspecies levels. Further studies should investigate vegetative propagation and heritability of nutritional and phytochemical traits before the use of seed for propagation.